Effectiveness of Powder and Solid Ragi Starter on Production of Bioethanol from Rice Straw Hydrolyzate - Ediviani, Wanda; Octavia, Silvi; Yasman, Yasman (Makara Journal of Science, 2014)
Rice straw is one of the most abundant forms of agricultural wastes in Indonesia. Rice straw contains polysaccharide in the form of cellulose and hemicellulose, which can be used as raw materials in the production of bioethanol. This study aims to examine the effectiveness of bioethanol production from rice straw’s hydrolyzate. Research was carried out by fermenting the sample using two types of starters (Baker's yeast, known as powder starter (F); and Tapai’s starter, known as solid starter (S) with a control of pure yeast, Saccharomyces cerevisiae. Glucose levels were measured using a glucometer, and bioethanol levels were analyzed using high-performance liquid chromatography (HPLC). In this study, split plot design was used as a data analyzer with two treatment factors: starter’s inoculum (R) and time of fermentation (T). This study shows that there is no significant difference between the starters’ levels of bioethanol production. However, S’s treatment produced higher levels (5,1 g/L) of bioethanol compared to F’s (4,8 g/L); the rate of bioethanol production in S’s treatment is also higher (1,3 g/L.h) than that in F’s (1,2 g/L.h). This study concludes that Tapai’s starter is more effective in producing bioethanol from rice straw’s hydrolyzate.